POLITICAL SATIRE ON SOCIAL MEDIA RESPONDING TO THE CONSTITUTIONAL COURT'S DECISION ON VICE PRESIDENT AGE ELIGIBILITY FOR THE 2024 ELECTIONS - Muntaha; Arianto, Puput (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research explains the political satire on Indonesian social media, focusing on the public's response to the constitutional court's decision regarding the vice president's age eligibility for the 2024 elections. Utilising Indonesia's three most prominent social media platforms, such as TikTok, Twitter, and YouTube, the research aims to unravel the various techniques for crafting and delivering political satire through visual and audiovisual media. A comprehensive analysis of 40 distinct satirical pieces was conducted to identify the different techniques. These pieces were collected using digital observation techniques across the specified platforms, supplemented by searches on Google. The methodological framework for the analysis is grounded in Buijzen and Valkenburg's (2004) typology for delivering humour. Our findings unveil a rich tapestry of satirical strategies employed by Indonesian netizens. At least seven distinct techniques were identified: irony, sarcasm, parody, puns, juxtaposition, slapstick, and metaphor. Irony emerged as the most prevalently used technique, indicating its effectiveness in nuanced political critiques. This research contributes to a deeper understanding of the interaction between humour and political discourse in the digital age, especially within the Indonesian context. It highlights the significance of satire as a powerful tool for political expression and engagement on social media.